Impacts of climate change on water management. Issue 3 (20th April 2022) - Fei, Chengcheng J.; McCarl, Bruce A.; Yang, Yingqian; Ayana, Essayas Kaba; Srinivasan, Raghavan; Lei, Yuhong; Li, Lingyi; Sheng, Bingru; Fan, Xinxin
Abstract: Climate change and increasing demands are stressing water allocation. In many places, water reallocation and expensive water development actions are being undertaken with more likely to be stimulated by climate change. Here we examine reallocation and development actions between and within municipal, agricultural, and energy industry users in a water‐scarce region and examine how climate change stimulates further actions. We built a regional agricultural, water and electricity two‐stage stochastic model that simulates optimal strategies in South Central Texas. We find that climate change significantly expands water development, causes agricultural water use reduction and reallocation to municipal interests.